Thermal buoyant smoke back-layering flow length in a longitudinal ventilated tunnel with ceiling extraction at difference distance from heat source. (5th March 2015) - Chen, L.F.; Hu, L.H.; Zhang, X.L.; Zhang, X.Z.; Zhang, X.C.; Yang, L.Z.
Abstract: Tunnel is a special long-narrow building structure. The thermal buoyancy-driven upstream reversing smoke back-layering flow produced by the burning of heat source is harmful for human evacuation. This paper reveals the effect of the distance between ceiling extraction (opening) distance and heat source on the thermally-driven smoke back-layering flow length beneath the ceiling in a tunnel with combination of ceiling extraction and longitudinal ventilation, which has not previously been reported. Experiments are conducted in a reduced-scale tunnel [72 m (length) × 1.5 m (width) × 1.3 m (height)]. A porous gas burner is used to provide steady heat source and its relative distance from the ceiling extraction (opening) is varied. It is found that the thermally-driven smoke back-layering flow length increases as the heat source-ceiling extraction (opening) distance increases. A new model is theoretically deduced to predict the smoke back-layering flow length including the factor of heat source-ceiling extraction (opening) distance, by accounting for the energy loss due to extraction which is calculated based on the local longitudinal temperature profile estimation. The predictions by the proposed model are in good agreement with the experimental results. Highlights: Thermally-driven back-layering flow length investigated by a 72 m long model tunnel. Combining effect of ceiling extraction and longitudinal force air flow concerned. A new model proposed concerning heat source-extraction opening distance. Proposed model agree well with the measured results.